2018
DOI: 10.1097/md.0000000000012368
|View full text |Cite
|
Sign up to set email alerts
|

The optimal anticoagulant therapy for mechanical heart valves in a gallbladder cancer patient with hepatic metastases

Abstract: Rationale:Developing an optimal anticoagulant strategy poses a challenging task in patients with mechanical heart valves (MHVs) throughout their lifetime. We report an optimal anticoagulant therapy in a cancer patient with hepatic metastases after MHV replacement.Patient concerns:A 68-year-old female with MHVs suffered from gallbladder cancer with hepatic metastases. Her international normalized ratio (INR) fluctuated owing to the declined hepatic function.Diagnoses:Gallbladder cancer and hepatic metastases, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In a systematic review covering 120 clinical trials and case reports, Seshadri et al concluded that LMWH can be used as a safe anticoagulant in pregnant females with mechanical heart valves [151]. Furthermore, in a case report by Yan et al, a patient with gallbladder cancer and hepatic metastases who could not remain on warfarin therapy was successfully maintained on LMWH therapy, providing the potential for therapy other than warfarin even in non-pregnant patients [152].…”
Section: Efficacy Of Different Anticoagulant Regiments With Mechanica...mentioning
confidence: 99%
“…In a systematic review covering 120 clinical trials and case reports, Seshadri et al concluded that LMWH can be used as a safe anticoagulant in pregnant females with mechanical heart valves [151]. Furthermore, in a case report by Yan et al, a patient with gallbladder cancer and hepatic metastases who could not remain on warfarin therapy was successfully maintained on LMWH therapy, providing the potential for therapy other than warfarin even in non-pregnant patients [152].…”
Section: Efficacy Of Different Anticoagulant Regiments With Mechanica...mentioning
confidence: 99%